2020
DOI: 10.22159/ijap.2020.v12s2.op-05
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Dentinal Tubular Penetration of Three Bioceramic Sealers

Abstract: Objective: The main objective of endodontic treatment is to remove microorganisms from the root canal space and prevents reinfection. Deep penetration of the dentinal tubule is advantageous because it increases the contact area between the root canal filling material and dentin, thereby increasing the sealing quality of the entire root canal system. Bioceramic sealers are biocompatible, nontoxic, non-shrinking, hydrophilic, and stable, do not expand during setting, and can form hydroxyapatite, which then forms… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
12
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(12 citation statements)
references
References 18 publications
0
12
0
Order By: Relevance
“…From there, 274 records were excluded upon screening the title and abstract. The 12 resulting articles were evaluated by reading their full text, and all 12 of them were considered as eligible for qualitative synthesis after full-text evaluation: [ 37 , 38 , 39 , 40 , 41 , 42 , 43 , 44 , 45 , 46 , 47 , 48 ] ( Figure 1 ). No additional studies were found upon the manual reference searching of eligible studies.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…From there, 274 records were excluded upon screening the title and abstract. The 12 resulting articles were evaluated by reading their full text, and all 12 of them were considered as eligible for qualitative synthesis after full-text evaluation: [ 37 , 38 , 39 , 40 , 41 , 42 , 43 , 44 , 45 , 46 , 47 , 48 ] ( Figure 1 ). No additional studies were found upon the manual reference searching of eligible studies.…”
Section: Resultsmentioning
confidence: 99%
“…One of the included studies [ 37 ] ultrasonically activated the sealers inside the root canals. All studies mixed the sealers with a fluorescent dye to allow visualization of the sealer penetration in the dental canals except one study [ 42 ] which did not mix the sealer with any dye. After root canal filling, all samples in all studies were stored in 100% humidity for 3–14 days and were later sectioned horizontally in different distances away from the apex to obtain samples from the apical, middle, and coronal thirds of the root.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Bioceramic sealer contains calcium phosphate silicate that has very small particles (<1 m) that is hydrophilic and this sealer can enter the lateral root canals and has and size of dentinal tubules, and the anatomy of the root canal system. 23 These factors also affect differences in the results of the penetration of each irrigating material of the bioceramic sealer and AH Plus sealer. Irrigation material should meet several requirements to become an ideal irrigation material, because this research is limited to knowing the effect of chitosan oligosaccharide irrigant on the penetration of root canal sealers, it is necessary to do further research such as evaluating the antibacterial effect of chitosan oligosaccharide irrigant on bacteria of the root canal, and examining the cleanliness of the dentin surface of the root canal after irrigation with oligosaccharide chitosan.…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, it has been shown that these materials can even promote bone regeneration [54] when accidentally extruded through the apical foramen during root canal filling procedures [55,56]. These materials have also the ability to establish a micromechanical retention by tag sealer penetration in dentinal tubules [57]. In the present study, the scanning electron microscope analysis confirmed a visible penetration of the bioceramic root canal sealer into the dentinal tubules: this behavior may help establishing a stronger physical barrier, improving retention of the root filling, entombing possible residual bacteria into dentinal tubules and, probably, enhancing the ultimate quality of the apical seal [35].…”
Section: Discussionmentioning
confidence: 99%